2017
DOI: 10.1007/s10934-017-0387-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of amine-impregnated mesoporous carbon with microporous activated carbon and 13X zeolite for biogas purification

Abstract: CH 4 . Depending on the process used during production, along with the type of fermented material, the composition of the produced gas can vary significantly. However, from an anaerobic digester, a significant portion of the produced gas will always be CO 2 . In order to enhance the gas stream for energy production processes, an adsorption process can be used to purify the individual components [1]. Purification of the gas mixtures to produce two high purity gas streams has the added benefit of producing a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As mentioned earlier, the most common methods for the preparation of supported amine adsorbents are (i) impregnation of amines on porous materials such as silica, 1 0 7 , 1 1 2 − 1 1 4 , 1 1 7 , 1 9 7 , 2 0 1 , 2 1 3 , 4 4 4 , 4 4 5 alumina, 4 4 6 activated carbon, 121,447,448 MOFs, 127 zeolites, 448,449 and clays, 450 and (ii) surface grafting of amine-containing species mostly on silica, 76,129,136−138 but occasionally on alumina 451 and other supports. 452 Other procedures such as amine tethering 144,145,148−153,205,408−416 and ligand modification [154][155][156]453 have also been used, particularly for MOFs.…”
Section: Amine-functionalized Adsorbentsmentioning
confidence: 99%
“…As mentioned earlier, the most common methods for the preparation of supported amine adsorbents are (i) impregnation of amines on porous materials such as silica, 1 0 7 , 1 1 2 − 1 1 4 , 1 1 7 , 1 9 7 , 2 0 1 , 2 1 3 , 4 4 4 , 4 4 5 alumina, 4 4 6 activated carbon, 121,447,448 MOFs, 127 zeolites, 448,449 and clays, 450 and (ii) surface grafting of amine-containing species mostly on silica, 76,129,136−138 but occasionally on alumina 451 and other supports. 452 Other procedures such as amine tethering 144,145,148−153,205,408−416 and ligand modification [154][155][156]453 have also been used, particularly for MOFs.…”
Section: Amine-functionalized Adsorbentsmentioning
confidence: 99%
“…To our knowledge, this is the only instance of the ZLC technique used to characterize the sorption kinetics of amino‐adsorbents. More recently, Brandani and coworkers utilized the ZLC method to measure irreversibly adsorbed CO 2 on the surface of amine‐grafted silicas and amine‐impregnated mesoporous carbons. The authors demonstrated that ZLC desorption curves can provide results comparable to calorimetric techniques for determining CO 2 uptakes.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based materials demonstrate widespread applications in industrial fields due to their wide variety of structures that permit the development of several materials for different applications [1]. Due to its characteristics of a high surface area and a pore diameter of less than 2 nm, activated carbon (AC) has widely been applied in adsorption [2], catalysis [3], purification [4], and separation [5], as well as a capacitor electrode [6]. However, uniformity with respect to the pore size, shape, and volume is crucial as these factors limit the separation ability of carbon materials for different-sized molecules [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, advances in mesoporous carbon materials [8] have led to the discovery of mesoporous carbon by the hard- [9] and soft- [5] template methods. Due to its excellent properties of electrical conductivity, inertness, thermal stability, high surface area, and superior pore structure, mesoporous carbon has been extensively used in industrial applications, such as energy storage [10], gas separation [4], CO 2 capture [11], and air and water purification [12][13][14][15]. Moreover, it is possible to control the pore size, volume, and surface area via the modification of synthetic methods.…”
Section: Introductionmentioning
confidence: 99%